PENGARUH MUTASI, PUNISHMENT, DAN JOB DESCRIPTION TERHADAP PRESTASI KERJA KARYAWAN PADA PT. MILANO BATANG SEPONGGOL - Octaviani, Yesi; Nasution, Ade Parlaungan (LPPM Universitas Labuhanbatu, 2020)
This study aims to examine and analyze the relationship between the effects of mutations, punishments, and job descriptions on employee performance at PT. Milano Batang Seponggol in South Labuhanbatu Regency. In this study, four variables were used, namely the Mutation (X1), Punishment (X2) and Job Description (X3) variables as the independent variable and the employee's Job Performance (Y) as the dependent variable. The sample in this study amounted to 75 respondents. To obtain data in statistical form using SPSS software version 16. The results of data processing show that the results of the coefficient Y = 14,602 + 0,264 X1 + 0,263 X2 + 0,161 X3 show Mutation (b1 = 0,264), Punishment (b2 = 0,263) and Job Description (b3 = 0.161) the correlation coefficient value was 67.6% and the determinant correlation was 43.3%. Testing the overall hypothesis F test (Simultaneous Test) by showing the value of Fcount is 19.866 with a significance level of 0.000. Therefore, the calculation with a significance level of 0.000